PENGEMBANGAN BUKU SAKU IPA BERBASIS PROBLEM BASED LEARNING DI UPTD SMP NEGERI 8 GUNUNGSITOLI - Zebua, Justin Intan Purnama Sari; Gulo, Hardikupatu; Waruwu, Toroziduhu; Harefa, Agnes Renostini; Lase, Natalia Kristiani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This study aims to develop a Science pocket book based on Problem-Based Learning (PBL) as a solution to the low conceptual understanding and learning motivation of students at UPTD SMP Negeri 8 Gunungsitoli. The research employed a Research and Development (R&D) method using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The needs analysis revealed that 80% of students considered the textbook less engaging, 90% required visual media, and 93% needed practical learning materials such as a pocket book. The product was developed through validation by material experts, language experts, and design experts, resulting in a “Highly Feasible” category with significant score improvements after revisions. The practicality test showed an average student response rate of 93.33% (“Highly Practical”). The implementation stage demonstrated increased motivation, engagement, and conceptual understanding in science learning. The effectiveness of the pocket book was also reflected in the student mastery level, which reached 93.02% in the field test. Thus, the developed PBL-based Science pocket book is proven to be feasible, practical, and effective as a learning medium to improve the quality of science instruction in junior high schools. ABSTRAK Penelitian ini bertujuan untuk mengembangkan buku saku IPA berbasis Problem-Based Learning (PBL) sebagai solusi atas rendahnya pemahaman konsep dan motivasi belajar peserta didik di UPTD SMP Negeri 8 Gunungsitoli. Penelitian menggunakan metode penelitian dan pengembangan (R&D) dengan model ADDIE yang meliputi tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Hasil analisis kebutuhan menunjukkan bahwa 80% peserta didik menilai buku paket kurang menarik, 90% membutuhkan media visual, dan 93% membutuhkan bahan ajar praktis seperti buku saku. Produk dikembangkan melalui validasi ahli materi, ahli bahasa, dan ahli desain yang menghasilkan kriteria Sangat Layak dengan peningkatan skor signifikan setelah revisi. Uji kepraktisan menunjukkan rata-rata respon siswa sebesar 93,33% (Sangat Praktis). Implementasi produk memperlihatkan peningkatan motivasi, keterlibatan, dan pemahaman konsep IPA. Efektivitas buku saku juga tercermin dari ketuntasan belajar siswa yang mencapai 93,02% pada uji lapangan. Dengan demikian, buku saku IPA berbasis PBL yang dikembangkan terbukti layak, praktis, dan efektif sebagai media pembelajaran untuk meningkatkan kualitas pembelajaran IPA di SMP.